Increased cytokine levels and histological changes in cartilage, synovial cells and synovial fluid after malleolar fractures. (October 2017) - Godoy-Santos, Alexandre L.; Ranzoni, Lucas; Teodoro, Walcy R.; Capelozzi, Vera; Giglio, Pedro; Fernandes, Tulio Diniz; Rammelt, Stefan
Abstract: Background: Malleolar fractures are among the most common fractures in the human skeleton with a high risk of later development of post-traumatic osteoarthritis (OA). The acute ankle injury initiates a sequence of events potentially leading to progressive articular surface damage resulting from inflammatory changes in cartilage, synovial tissue and synovial fluid. We hypothesised that in the acute phase of ankle fracture, these changes occur at the same time in the different tissues. Methods: Specimens of chondral tissue, synovial tissue and synovial fluid were collected from 16 patients with acute articular ankle fracture (study group). Additional samples were obtained from five male fresh cadavers within 12 hours of death (control group). Chondral tissue was assessed for cellularity, irregularities and chondrocyte disarray. Synovial tissue was assessed for synovitis, proteoglycans and collagen deposition. Synovial fluid was assessed for cytokines IL-2, IL-6, IL-10, IL-17, IFN-γ and TGF-β1. Results: Chondral tissue showed discontinuity in the tidemark between cartilage and subchondral bone, chondrocyte disarray, increased cellularity (both at the cartilage surface and subchondral bone), articular surface irregularities and increased deposition of proteoglycans and collagen fibres. Synovial tissue showed a statistically significant difference between the study and control groups in the concentration per tissue area of both thin collagen fibres (p=0.0274) and thick collagen fibres (p<0.0001). Cytokine concentrations in synovial fluid samples were significantly higher in ankle fracture tissue compared with controls for IL-2 (p=0.0002), IL-6 (p<0.0001), IL-10 (p=0.002) and IL-17 (p<0.0001). No statistically significant differences were observed for IFN-γ (p=0.06303) and TGF-β1 (p=0.8832). Conclusion: We observed a pattern of simultaneous and interrelated pathological changes in cartilage, subchondral bone, synovial tissue and synovial fluid after acute malleolar fracture. As the observed inflammatory changes could lead to the development of OA, a more thorough knowledge of these early processes could be helpful to find strategies for prevention or delay of this common complication.